Male Perception and Participation in Family Planning Among Tribal Communities of Maharashtra, India: A Mixed-Method Study. (April 2020) - Jungari, Suresh; Paswan, Balram
This study examined male perceptions and awareness about family planning. The study also investigated male involvement in family planning and contraceptive use decision-making. Furthermore, in this study, we assessed men's awareness, attitude, and practice of modern contraceptive methods and determined the level of spousal communication. In this study, a field survey was conducted among the tribal population of Maharashtra. Both qualitative and quantitative methods were used for data collection. A sample of 385 men whose wives had given birth in the last 2 years were interviewed. Almost two thirds of the surveyed men (64%) had heard about modern family planning. The main source of information for family planning was the multipurpose worker in the village for 48% of men, followed by friends 16% and the auxiliary nurse midwife and accredited social health activist for 11% and 10%, respectively. Results show that the current use of any modern family planning method, including male and female methods, was 18.4%. Among the currently used modern methods, the major modern family planning method was male sterilization (67%), followed by oral pills (11%) and male condom use (10%). This study indicated that the acceptance of male modern family planning methods is very high.